Sjafruddin Prawiranegara's Leadership and Ethics in the PDRI Period - Sudirman Sudirman; Destel Meri; Dedi Asmara (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
The Period of the Emergency Government of the Republic of Indonesia (PDRI) in December 1948-July 1949 was a red thread from the presence of present-day Indonesia. Sjafruddin Prawiranegara, who previously served as Minister of Welfare, was then asked to become the Chair of the PDRI, or the same level as the position of a President. The purpose of this study is to see the extent of the influence of Sjafruddin's leadership and the ethical values he demonstrated when he led PDRI in the jungles of Central Sumatra. The method used in this research is historical method consisting of heuristics, criticism, interpretation, and historiography. During his leadership, the entire region was given the status of a military government emergency. Uniquely, in Java the civil administration is held by the military, and in Sumatra each administrative area uses the word military in its position. During the eight months of his reign, Sjafruddin has shown ethical values as a head of state, such as integrity, patriotic and nationalist, selfless struggle, and simplicity.